Possible Protective Effect of Hydroxychloroquine on Retarding the Occurrence of Integument Damage in Lupus: Data from LUMINA, a Multiethnic Cohort - Pons-Estel, Guillermo J. (2010)
OBJECTIVE: To determine the features predictive of time-to-integument damage in patients with systemic lupus erythematosus (SLE) from a multiethnic cohort (LUMINA). METHODS: SLE LUMINA patients (n=580), age ≥16 years, disease duration ≤5 years at baseline (T0), of African American, Hispanic and Caucasian ethnicity were studied. Integument damage was defined per the SLICC damage index (scarring alopecia, extensive skin scarring and skin ulcers lasting at least six months); factors associated with time-to-its occurrence were examined by Cox proportional univariable and multivariable (main model) hazards regression analyses. Two alternative models were also examined; in model 1 all patients, regardless of when integument damage occurred (n=94), were included; in model 2 a time-varying approach (GEE) was employed. RESULTS: Thirty-nine (6.7%) of 580 patients developed integument damage over a mean (SD) total disease duration of 5.9 (3.7) years and were included in the main multivariable regression model. After adjusting for discoid rash, nailfold infarcts, photosensitivity and Raynaud’s phenomenon (significant in the univariable analyses), disease activity over time [Hazard ratio (HR)=1.17; 95% Confidence interval (CI) 1.09–1.26)] was associated with a shorter time-to-integument damage whereas hydroxychloroquine use (HR=0.23, 95% CI 0.12–0.47) and Texan-Hispanic (HR=0.35; 95% CI 0.14–0.87) and Caucasian ethnicities (HR=0.37; 95% CI 0.14–0.99) were associated with a longer time. Results of the alternative models were consistent with those of the main model albeit in model 2 the association with hydroxychloroquine was not significant. CONCLUSIONS: Our data indicate that hydroxychloroquine use is possibly associated with a delay in integument damage development in patients with SLE.